Are Remote Sensing Evapotranspiration Models Reliable Across South American Ecoregions?. Issue 11 (10th November 2021) - Melo, D. C. D.; Anache, J. A. A.; Borges, V. P.; Miralles, D. G.; Martens, B.; Fisher, J. B.; Nóbrega, R. L. B.; Moreno, A.; Cabral, O. M. R.; Rodrigues, T. R.; Bezerra, B.; Silva, C. M. S.; et al.
Abstract: Many remote sensing‐based evapotranspiration (RSBET) algorithms have been proposed in the past decades and evaluated using flux tower data, mainly over North America and Europe. Model evaluation across South America has been done locally or using only a single algorithm at a time. Here, we provide the first evaluation of multiple RSBET models, at a daily scale, across a wide variety of biomes, climate zones, and land uses in South America. We used meteorological data from 25 flux towers to force four RSBET models: Priestley–Taylor Jet Propulsion Laboratory (PT‐JPL), Global Land Evaporation Amsterdam Model (GLEAM), Penman–Monteith Mu model (PM‐MOD), and Penman–Monteith Nagler model (PM‐VI). E T was predicted satisfactorily by all four models, with correlations consistently higher ( R 2 > 0.6 ) for GLEAM and PT‐JPL, and PM‐MOD and PM‐VI presenting overall better responses in terms of percent bias ( − 10 < P B I A S < 10 %). As for PM‐VI, this outcome is expected, given that the model requires calibration with local data. Model skill seems to be unrelated to land‐use but instead presented some dependency on biome and climate, with the models producing the best results for wet to moderately wet environments. Our findings show the suitability of individual models for a number of combinations of land cover types, biomes, and climates. At the same time, no model outperformed the others for all conditions, which emphasizes the need for adapting individual algorithms to take into account intrinsic characteristics of climates and ecosystems in South America. Key Points: Four remote sensing evapotranspiration (ET) models were evaluated using 25 flux towers from across South America Performance of all models is reduced in dry environments Comparisons with flux tower‐based ET showed that Global Land Evaporation Amsterdam Model and Priestley–Taylor Jet Propulsion Laboratory produced higher correlations whereas RMSE was similar for all models